Organic Anion Transporting Polypeptides 1B1 and 1B3 Play an Important Role in Uremic Toxin Handling and Drug-Uremic Toxin Interactions in the Liver - Toshihiro Sato; Hiroaki Yamaguchi; Takuma Kogawa; Takaaki Abe; Nariyasu Mano (Frontiers Media S.A., 2014)
PURPOSE. Organic anion-transporting polypeptide (OATP) 1B1 and OATP1B3 contribute to hepatic uptake of numerous drugs. Thus, reduced OATP1B1 and OATP1B3 activity in chronic kidney disease (CKD) may have a major impact on the hepatic clearance of drugs. The effect of drug-uremic toxin interactions on OATP1B1 and OATP1B3 has not been well studied. In the present study, we examine the inhibitory effects of uremic toxins on OATP1B1 and OATP1B3 transport activity to evaluate the interactions between drugs and uremic toxins in patients with chronic kidney disease. METHODS. [3H]Estron-3-sulfate, [3H]taurocholate uptake and [3H]methotrexate by OATP1B1 and OATP1B3 expressing HEK293 cells were performed to evaluate the inhibitory effect of uremic toxins. To clarify whether the uremic toxins that interact with OATP1B1 and/or OATP1B3 were substrates for these transporters, we performed uptake studies. RESULTS. Four uremic toxins, kynurenic acid, indole-3-acetic acid, indoxyl sulfate, and p-cresol, inhibited OATP1B1- and OATP1B3-mediated transport in a concentration-dependent manner, with IC50 values of 180, 770, 2700, and 4600 µM, respectively, for OATP1B1 and 180, 1100, 1300, and 1700 µM, respectively, for OATP1B3. [3H]Methotrexate uptake by OATPs was also inhibited by the four uremic toxins in a dose-dependent manner. Uptake studies revealed that kynurenic acid is a substrate for both the OATP1B1 and OATP1B3. Moreover, OATP1B3 was involved in the transport of indoxyl sulfate. Indole-3-acetic acid and p-cresol were not significantly transported by OATP1B1 and OATP1B3. CONCLUSIONS. We showed that some uremic toxins inhibit OATP-mediated uptake in a concentration-dependent manner, and clarified OATPs contribution to uremic toxin handling in the liver. Thus, we provided basic information to estimate the inhibitory effects of uremic toxins on OATPs in CKD patients. These data suggest that the dose of drugs excreted via renal and non-renal pathways should be carefully adjusted in CKD patients. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.